Pengaruh Limbah Fly Ash Dari Serbuk Arang Briket Terhadap Beton Geopolimer - Luthfianto, Arroyan, Ir. Suhendro Trinugroho, M.T (2016)
Concrete is the most important element in a construction work. Geopolymer concrete is a type of concrete that is 100% not using cement. Fly ash from the combustion of coal is used as a source of material to make the binder required in the concrete mix. Binder is a binder in geopolymer concrete mixture consisting of fly ash and alkaline activator, fly ash used in this study using charcoal briquette powder obtained from the combustion residue of coal briquettes used is that through sieve no. 200, while the activator alkaline as a binder elements aluminum and silicate contained in fly ash to form a bond olymerization, the activator is very important for the binding elements of aluminum and silicate contained in the powder of charcoal briquettes, activator used is sodium hydroxide that serves to react elements to produce polymer powders bond charcoal briquettes and sodium silicate which has the function of accelerating the polymerization reaction. The purpose of this study for influence briquette charcoal powder to the geopolymer concrete, as well as get a compressive strength of geopolymer concrete and seek optimum time to time mixing. Comparisons are used to aggregate: binder 85:15, 80:20, 75:25, 70:30, and 65:35 respectively mixing time is 7.5 minutes and 15 minutes. Of testing variations optimum compressive strength contained in the variation of 70:30, 70:30 mixing time of 7.5 minutes to produce 3.510 MPa compressive strength while generating the mixing time 75:25 2.689 MPa compressive strength, the optimum time for mixing is 7.5 minutes. Key words: activator, binder, briquette, compressive strength, geopolymer